A highly sensitive compact liquid sensor based on slotted phononic crystal plates. Issue 23 (26th October 2016) - Wang, Chen; Cai, Feiyan; Li, Fei; Meng, Long; Li, Jiangyu; Wu, Junru; Kang, Yan; Zheng, Hairong
Abstract : We report a slotted phononic crystal plate (SPCP) sensor detecting a small amount of liquid sample with a high sensitivity. Abstract : Liquid sensing is achieved by using slotted phononic crystal plates (SPCP). The sensing mechanism is based on the fact that an acoustic wave confined in a small liquid slot intensively interacts with the liquid sample in the slot, and the acoustic energy flux transmission spectrum of the SPCP system strongly depends on the acoustic properties of the liquid in the slot. Consequently, the resonance frequency of the sensing system varies with the density and sound velocity of the liquid sample. Compared with the traditional Lamb wave sensor, the SPCP sensor exhibits a higher sensitivity and requires a minimal amount of liquid sample. These attractive advantages may allow the SPCP liquid sensor to be easily integrated into a chip for broad lab-on-chip biochemical sensing applications.